Construction of a composite photocatalyst with significantly enhanced photocatalytic performance through combination of homo-junction with hetero-junction. Issue 2 (12th December 2017) - Guo, Yan; Wang, Peifang; Qian, Jin; Hou, Jun; Ao, Yanhui; Wang, Chao
Abstract : BiOCl modified twinned BiPO4 exhibited significantly enhanced photocatalytic activity because of the synergistic effect of homo-junction and hetero-junction. Abstract : Twinned BiPO4 has been confirmed to exhibit higher performance than pristine single-phase BiPO4 (HBIP) owing to the formation of a homo-junction between monazite monoclinic BiPO4 (nMBIP) and monoclinic BiPO4 (mMBIP). In the present study, further promotion of photocatalytic activity of twinned BiPO4 was achieved by coupling with BiOCl because of the formation of multi-junctions with a ladder band structure. The results showed that the photocatalytic activity of twinned BiPO4 enhanced 8.7 times and 2.5 times compared to that of pristine BiPO4 for degradation of methyl orange (MO) and acetaminophen (ACE), respectively, while the photocatalytic activity of the obtained multi-junctioned sample enhanced 35.7 times and 59.5 times compared to that of twinned BiPO4 for degradation of MO and ACE, respectively. XRD and Raman spectra revealed that the composites exhibited characteristic peaks of BiOCl and BiPO4 including nMBIP and mMBIP. In addition to the homo-junction between nMBIP and mMBIP, the hetero-junction between twinned BiPO4 and BiOCl was verified in the composites by TEM and HRTEM. The boosted transfer and separation of photo-excited charge carriers were attributed to the synergy between the homo-junction and hetero-junction in the composite, which were measured by the transient photocurrent response, EIS and PL. Consequently, the corresponding photocatalytic performance was notably improved. This work provides a new concept to design new multi-junctioned photocatalysts with both homo- and hetero-junctions for efficient pollutant removal in environmental renovation.